Prevalence of Anxiety and Depression Among Patients with Coronary Artery Bypass Grafting (CABG) in Karnataka and Kerala (International Journal of Physiotherapy, 2024)
Background: Anxiety is a shared sense of unease that many individuals go through in their lives. Pre-cardiac surgery anxiety can result in several problems, including a poor prognosis, morbidity, and a lower quality of life. Due to several variables like low economic position, fear of dying, dread of being admitted to the intensive care unit, etc., anxiety is widespread among CABG patients. One of the main concerns for patients undergoing CABG is anxiety control. Subjective assessments and clinical results are used to screen for anxiety. The care provider team will be able to find some workable strategies to lessen anxiety and assist the patient in the future with pre-operative evaluation. Globally, the anxiety in patients undergoing CABG has been determined by numerous studies. However, the available data is currently sparse. Nevertheless, there isn't much evidence to support this claim in the Indian context. Furthermore, Data on the prevalence of anxiety is lacking in the southern region of India in the literature. Thus, the purpose of this study is to identify anxiety in patients receiving CABG in Kerala and Karnataka, South India. The objective of the study is to determine the prevalence of anxiety among CABG patients in states such as Kerala and Karnataka. Also, to find out the correlation between anxiety and depression between age, gender, and BMI among patients undergoing CABG.Methods: Patients undergoing CABG are asked for their consent. Based on the inclusion criteria, 120 (84 males and 36 females) patients scheduled for CABG were included in the study out of the 125 patients screened. Patients provide baseline information. Patients with a history of anxiety disorders and those using anxiolytics were excluded. Individuals receiving anxiolytics may exhibit symptoms if they are not taking their prescription as prescribed, which could potentially impact the study's outcomes. Patients are, therefore, not included. The Hospital Anxiety and Depression Scale (HADS) was used to evaluate the patients' anxiety. Patients who received a score higher than eight are assigned to the anxiety group.Results: Descriptive statistics are employed to analyze the data. The results showed that the mean anxiety score was 10.2, and the mean depression score was 6.7. A significant correlation exists between the frequency of anxiety and gender, with a p-value less than 0.05.Conclusions: Before surgery, patients undergoing CABG experience anxiety. In these situations, prompt assessment and management are necessary.